Apparatuses of observation and occupation: Settler colonialism and space science in Hawai'i. (October 2021) - Sammler, Katherine G; Lynch, Casey R
This paper examines two space science infrastructures in Hawai'i, the Thirty Meter Telescope (TMT) and the Hawai'i Space Exploration Analog and Simulation (HI-SEAS). It considers how scientific observation and colonial occupation are co-constituted through the production of apparatuses – extensive material practices and arrangements that iteratively produce subject–object relations. By analyzing TMT and HI-SEAS as apparatuses, we show how both involve the active ordering of space, time, and matter in ways that are dependent upon existing settler colonial relations while enacting specific subject positions key to the projection of settler colonialism across space and time. TMT materializes the Archimedean point, or view-from-nowhere, on which Western scientific "objectivity" depends, while HI-SEAS works to produce ideal colonizer-subjectivities and orient their bodies to the spatialities of the colony. Engaging Native Hawai'ian, Indigenous, and allied anti-colonial critiques, we argue that social science of outer space research must critically address the colony, as its basic logics are foundational to the practices of contemporary space science and imaginaries of space exploration.